Key based on liquid silica gel and preparation method thereof
By modifying the polymeric anti-aging agent macromolecules that modify silicon oxygen bonds on the surface of nano-silicon nitride, and combining the modified inorganic enhancer with liquid silicone, the problem of poor waterproof performance caused by the prone to aging of the volume bonds of mobile phones is solved, and the improvement of high strength and anti-aging performance is achieved.
Patent Information
- Application Number
- CN202510694690.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-08-12
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The current mobile phone volume keys have poor waterproof performance, and the silicone material is prone to aging, resulting in a tight seal, which affects the waterproof effect of the mobile phone.
The modified inorganic reinforcement is used to combine with liquid silicone, and polymerized anti-aging macromolecules that modify silicon oxygen bonds on the surface of nano-silicon nitride to form a winding structure to improve the strength and anti-aging properties of silicone gel.
The prepared buttons have high strength and excellent anti-aging performance, which improves the waterproof performance of the mobile phone volume keys.
Smart Images

Figure CN120464209A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicone rubber, and in particular to a liquid silicone-based keypad and a preparation method thereof. Background Art
[0002] With the widespread use of smartphones, people have increasingly higher requirements for the performance and quality of mobile phones. Among them, the waterproof performance of mobile phones is an important consideration. In daily life, mobile phones may come into contact with water, such as rain, sweat, and accidentally splashed liquids. If the waterproof performance of the mobile phone is poor, water may enter the interior of the phone, causing short circuits and damage to electronic components, thereby affecting the normal use of the phone and shortening the service life of the phone. At present, the waterproof measures of mobile phones are mainly focused on the overall sealing design of the body. Although there are some waterproof designs for external buttons such as the volume button of the mobile phone, the results are often unsatisfactory. Therefore, there is an urgent need to develop a new waterproof process for the volume button of mobile phones to improve the overall waterproof performance of mobile phones.
[0003] Currently, external buttons on mobile phones, such as volume buttons, are typically made of metal and plastic, often requiring sealing with materials like rubber pads. This sealing method is prone to leaks. Therefore, developing new button materials is crucial to solving the problem of waterproofing mobile phones. Silicone, due to its high elasticity, can achieve a perfect fit with the phone casing, thus achieving a waterproof effect. However, silicone is prone to aging and will inevitably deform over time. Therefore, modifying silicone to improve its aging resistance is of great significance. Summary of the Invention
[0004] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a liquid silicone-based keypad and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A liquid silicone-based keypad comprising a component A and a component B;
[0007] The component A comprises the following raw materials in parts by weight: 75-90 parts of liquid silicone rubber, 1-2 parts of a cross-linking agent, and 2-6 parts of a modified inorganic reinforcing agent;
[0008] The B component is a catalyst;
[0009] The weight ratio of the component A to the component B is 1:0.01-0.03.
[0010] As a further embodiment of the present invention, the liquid silicone is vinyl polysiloxane.
[0011] As a further embodiment of the present invention, the cross-linking agent is any one of hydrogen-containing silicone oil, methyl hydrogen-containing silicone resin or phenyl hydrogen-containing silicone resin.
[0012] As a further embodiment of the present invention, the preparation method of the modified inorganic reinforcing agent comprises the following steps:
[0013] Step 1: Add a silane coupling agent containing an epoxy group to a sulfuric acid solution with a pH of 2-3, start stirring after the addition is completed, mix evenly, heat to 90-95°C, continue stirring for 0.5-1h, then reduce the temperature to 50-60°C, add nano-silicon nitride, disperse evenly, increase the temperature to 60-70°C, keep warm for 4-8h, cool and discharge to obtain hydroxyl-modified nano-silicon nitride;
[0014] Step 2: Add hydroxyl-modified nano-silicon nitride to a toluene medium and ultrasonically disperse it to form a uniform dispersion. Then, add 5-hexenylmethyldichlorosilane and a catalyst to the dispersion. After the addition is completed, heat it to 60-70°C and keep it warm for 2-4 hours. Then, add an anti-aging chain extender to the dispersion, continue to keep it warm for 16-24 hours, cool it down and discharge it. The product is collected by centrifugation, washed, and vacuum-dried to obtain a modified inorganic reinforcing agent.
[0015] As a further embodiment of the present invention, in step 1, the epoxy group-containing silane coupling agent is 3-glycidyloxypropyltrimethylsilane or 3-glycidyloxypropyltriethylsilane.
[0016] As a further embodiment of the present invention, in step 2, the catalyst is triethylamine.
[0017] As a further solution of the present invention, in step 2, the preparation method of the anti-aging chain extender is as follows:
[0018] Add p-aminodiphenylamine, glycidol and tetrahydrofuran to the reaction kettle. After the addition is completed, start stirring until a uniform reaction liquid is formed. Then start heating and raise the temperature to 60-65°C. After keeping warm and stirring for 6-9 hours, stop heating, remove the solvent by rotary evaporation, collect the product, and undergo post-processing and purification to obtain an anti-aging chain extender.
[0019] As a further embodiment of the present invention, the molar ratio of p-aminodiphenylamine to glycidol is 1:1.
[0020] As a further embodiment of the present invention, the catalyst is a platinum catalyst.
[0021] In the above technical scheme, first, under the action of sulfuric acid solution, the epoxy groups in the structure of the silane coupling agent containing epoxy groups are ring-opened to form hydroxyl substituents, and then the siloxane groups in its structure are used to modify the surface of the nano-silicon nitride to obtain nano-silicon nitride with active hydroxyl substituents on the surface. Then, 5-hexenylmethyldichlorosilane is used as a linker, and under the action of a catalyst, it first replaces the hydroxyl groups on the surface of the nano-silicon nitride, and continuously and uninterruptedly replaces the two equivalents of active hydroxyl groups in the structure of the antioxidant chain extender, and then modifies the surface of the nano-silicon nitride with polymeric antioxidant macromolecules connected by silicon-oxygen bonds to obtain a modified inorganic reinforcing agent.
[0022] The anti-aging chain extender is prepared by using p-aminodiphenylamine and glycidol as reactants, and the primary amino groups and epoxy groups in each other's structures undergo ring opening to obtain an anti-aging chain extender containing two equivalents of active hydroxyl substituents in the structure.
[0023] A method for preparing a button based on liquid silicone comprises the following steps:
[0024] The first step is to mix component A and component B, and stir them mechanically to form a premix;
[0025] The second step is to inject the premix into the molding die, and then perform a vacuum treatment to make the premix completely fill the cavity of the molding die;
[0026] The third step is to place the forming mold in a temperature environment of 100-150℃ to allow the premix to completely solidify and then demould.
[0027] Beneficial effects of the present invention:
[0028] The present invention prepares a modified inorganic reinforcing agent by modifying the surface of nano-silicon nitride with polymeric antioxidant macromolecules connected by silicon-oxygen bonds. The modified inorganic reinforcing agent is used as an additive for liquid silicone. During the subsequent heating and curing process, the unsaturated olefin groups contained in the polymeric antioxidant macromolecular structure can interact with the cross-linking agent, thereby forming a entangled structure with the silicone molecular chain, prompting the nano-silicon nitride to exist in the material in the form of cross-linking support points, effectively exerting its own reinforcement advantages, and making the prepared key have high strength characteristics. In addition, due to the confinement effect between the polymeric antioxidant macromolecules and the matrix, they cannot easily migrate out of the matrix. Therefore, the anti-aging effect of the polymeric antioxidant itself can be utilized to improve the anti-aging performance of the key.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is the infrared analysis test diagram of the anti-aging chain extender. DETAILED DESCRIPTION
[0032] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0033] Example 1
[0034] A liquid silicone-based keypad comprising a component A and a component B;
[0035] The component A comprises the following raw materials in parts by weight: 75 parts of vinyl polysiloxane, 1 part of hydrogenated silicone oil, and 2 parts of modified inorganic reinforcing agent;
[0036] The B component is a platinum catalyst;
[0037] The weight ratio of the component A to the component B is 1:0.02.
[0038] The method for preparing the key comprises the following steps:
[0039] The first step is to mix component A and component B, and stir them mechanically to form a premix;
[0040] The second step is to inject the premix into the molding die, and then perform a vacuum treatment to make the premix completely fill the cavity of the molding die;
[0041] The third step is to place the forming mold in a temperature environment of 120°C to allow the premix to completely solidify and demould.
[0042] Example 2
[0043] A liquid silicone-based keypad comprising a component A and a component B;
[0044] The component A comprises the following raw materials in parts by weight: 80 parts of vinyl polysiloxane, 1.5 parts of hydrogenated silicone oil, and 5 parts of modified inorganic reinforcing agent;
[0045] The B component is a platinum catalyst;
[0046] The weight ratio of the component A to the component B is 1:0.02.
[0047] The method for preparing the key comprises the following steps:
[0048] The first step is to mix component A and component B, and stir them mechanically to form a premix;
[0049] The second step is to inject the premix into the molding die, and then perform a vacuum treatment to make the premix completely fill the cavity of the molding die;
[0050] The third step is to place the forming mold in a temperature environment of 120°C to allow the premix to completely solidify and demould.
[0051] Example 3
[0052] A liquid silicone-based keypad comprising a component A and a component B;
[0053] The component A comprises the following raw materials in parts by weight: 90 parts of vinyl polysiloxane, 2 parts of methyl hydrogenated silicone resin, and 6 parts of modified inorganic reinforcing agent;
[0054] The B component is a platinum catalyst;
[0055] The weight ratio of the component A to the component B is 1:0.02.
[0056] The method for preparing the key comprises the following steps:
[0057] The first step is to mix component A and component B, and stir them mechanically to form a premix;
[0058] The second step is to inject the premix into the molding die, and then perform a vacuum treatment to make the premix completely fill the cavity of the molding die;
[0059] The third step is to place the forming mold in a temperature environment of 120°C to allow the premix to completely solidify and demould.
[0060] The modified inorganic reinforcing agent in the above embodiment is prepared by the following method:
[0061] Step 1: Add 1.5 g of 3-glycidyloxypropyltriethylsilane to 50 mL of sulfuric acid solution with a pH of 2. After the addition is complete, stir and mix evenly. Then, heat to 90°C and continue stirring for 1 hour. Then, reduce the temperature to 55°C, add 2.5 g of nano-silicon nitride, disperse evenly, increase the temperature to 65°C, keep warm for 6 hours, cool and discharge to obtain hydroxyl-modified nano-silicon nitride.
[0062] Step 2: Add 1.8 g of hydroxyl-modified nano-silicon nitride to a toluene medium and ultrasonically disperse it to form a uniform dispersion. Then, add 6.5 g of 5-hexenylmethyldichlorosilane and 0.5 g of triethylamine to the dispersion. After the addition is completed, heat it to 65°C and keep it warm for 3 hours. Then, add 5 g of an anti-aging chain extender to the dispersion, continue to keep it warm for 18 hours, cool it down and discharge it. The product is collected by centrifugation, washed, and vacuum-dried to obtain a modified inorganic reinforcing agent.
[0063] The preparation method of the anti-aging chain extender is as follows:
[0064] Add 0.3g of p-aminodiphenylamine, 0.12g of glycidol and tetrahydrofuran to the reactor. After the addition, start stirring until a uniform reaction liquid is formed, turn on the heating, raise the temperature to 65°C, keep stirring for 8 hours, stop heating, remove the solvent by rotary evaporation, collect the product, and obtain an anti-aging chain extender through a post-processing purification process.
[0065] Figure 1 This is the infrared analysis test chart of the anti-aging chain extender, where 3331cm -1 The characteristic absorption peak at 3259 cm is attributed to the NH characteristic absorption peak of secondary ammonia. -1 The characteristic absorption peak at 3000-3100 cm is attributed to the characteristic absorption peak of hydroxyl. -1 The characteristic absorption peak at is attributed to the CH of the benzene ring.
[0066] Comparative Example 1
[0067] A liquid silicone-based keypad comprising a component A and a component B;
[0068] The component A comprises the following raw materials in parts by weight: 80 parts of vinyl polysiloxane, 1.5 parts of hydrogenated silicone oil, and 5 parts of nano-silicon nitride;
[0069] The B component is a platinum catalyst;
[0070] The weight ratio of the component A to the component B is 1:0.02.
[0071] The method for preparing the key comprises the following steps:
[0072] The first step is to mix component A and component B, and stir them mechanically to form a premix;
[0073] The second step is to inject the premix into the molding die, and then perform a vacuum treatment to make the premix completely fill the cavity of the molding die;
[0074] The third step is to place the forming mold in a temperature environment of 120°C to allow the premix to completely solidify and demould.
[0075] Comparative Example 2
[0076] A liquid silicone-based keypad comprising a component A and a component B;
[0077] The component A comprises the following raw materials in parts by weight: 80 parts of vinyl polysiloxane, 1.5 parts of hydrogenated silicone oil, and 5 parts of nano-silicon nitride;
[0078] The B component is a platinum catalyst;
[0079] The weight ratio of the component A to the component B is 1:0.02.
[0080] The method for preparing the key comprises the following steps:
[0081] The first step is to mix component A and component B, and stir them mechanically to form a premix;
[0082] The second step is to inject the premix into the molding die, and then perform a vacuum treatment to make the premix completely fill the cavity of the molding die;
[0083] The third step is to place the forming mold in a temperature environment of 120°C to allow the premix to completely solidify and demould.
[0084] Performance Testing
[0085] With reference to the standard GB / T 528-2009, tensile performance tests were conducted at a tensile rate of 500 mm / min. After the test, products from the same batch were placed in an oven at 150°C for accelerated aging for 24 hours. The products were then taken out and the tensile performance was tested again to evaluate the product's anti-aging performance.
[0086] Refer to standard GB / T 528-2008 for tear strength test;
[0087] The test results are recorded in the following table:
[0088]
[0089]
[0090] Analysis and test results show that the product prepared by using the modified inorganic reinforcing agent of the present invention as an additive has obviously excellent mechanical strength and better anti-aging performance. When nano silicon nitride without surface modification is directly used as an additive, the anti-aging effect brought by the polymeric antioxidant macromolecules cannot be utilized, and good compatibility cannot be achieved between each other. Therefore, all performances are significantly reduced.
[0091] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal description of the claims, or if they include equivalent structural elements that are not substantially different from the literal description of the claims, then these other embodiments should also be included in the scope of the claims.
[0092] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A key based on liquid silicone, characterized in that: It includes component A and component B; The component A comprises the following raw materials in parts by weight: 75-90 parts of liquid silicone rubber, 1-2 parts of a cross-linking agent, and 2-6 parts of a modified inorganic reinforcing agent; The B component is a catalyst; The weight ratio of the component A to the component B is 1:0.01-0.
03.
2. The liquid silicone-based button according to claim 1, characterized in that: The liquid silicone is vinyl polysiloxane.
3. The liquid silicone-based button according to claim 1, characterized in that: The cross-linking agent is any one of hydrogen-containing silicone oil, methyl hydrogen-containing silicone resin or phenyl hydrogen-containing silicone resin.
4. The liquid silicone-based key according to claim 1, characterized in that: The preparation method of the modified inorganic reinforcing agent comprises the following steps: Step 1: pretreating the epoxy group-containing silane coupling agent with a sulfuric acid solution, and then using the obtained product to perform surface modification on nano-silicon nitride to obtain hydroxyl-modified nano-silicon nitride; Step 2: Using 5-hexenylmethyldichlorosilane as a linker, in a toluene medium, by using a catalyst, first connect the hydroxyl-modified nano-silicon nitride, then add an anti-aging chain extender and carry out chain extension polymerization with an excess of 5-hexenylmethyldichlorosilane to obtain a modified inorganic reinforcing agent.
5. The liquid silicone-based key according to claim 4, characterized in that: In step 1, the epoxy group-containing silane coupling agent is 3-glycidyloxypropyltrimethylsilane or 3-glycidyloxypropyltriethylsilane.
6. The liquid silicone-based key according to claim 4, characterized in that: In step 2, the catalyst is triethylamine.
7. The liquid silicone-based key according to claim 4, characterized in that: In step 2, the preparation method of the anti-aging chain extender is as follows: Add p-aminodiphenylamine, glycidol and tetrahydrofuran to the reaction kettle. After the addition is completed, start stirring until a uniform reaction liquid is formed. Then start heating and raise the temperature to 60-65°C. After keeping warm and stirring for 6-9 hours, stop heating, remove the solvent by rotary evaporation, collect the product, and undergo post-processing and purification to obtain an anti-aging chain extender.
8. The liquid silicone-based key according to claim 7, characterized in that: The molar ratio of p-aminodiphenylamine to glycidol is 1:
1.
9. The liquid silicone-based button according to claim 1, characterized in that: The catalyst is a platinum catalyst.
10. A method for preparing a liquid silicone-based button according to claim 1, characterized in that: The following steps are involved: The first step is to mix component A and component B, and stir them mechanically to form a premix; The second step is to inject the premix into the molding die, and then perform a vacuum treatment to make the premix completely fill the cavity of the molding die; The third step is to place the forming mold in a temperature environment of 100-150℃ to allow the premix to completely solidify and then demould.
Citation Information
Patent Citations
Wear-resistant silicone rubber key and production process thereof
CN111154272A
Conductive silica gel, preparation method thereof and silica gel key
CN113563723A
Novel anti-aging agent as well as preparation method and application thereof
CN113956538A
Long-life high-resilience liquid silica gel
CN114591627A
Rubber for gas mask body
CN114685903A